Exploring the world of J.S. Bach : a traveler's guide - Marshall, Robert Lewis; Marshall, Traute M., 1942- (University of Illinois Press, 2016)
A singular resource, Exploring the World of J.S. Bach puts Bach aficionados and classical music lovers in the shoes of the master composer. Bach scholar Robert L. Marshall and veteran writer-translator Traute M. Marshall lead readers on a Baroque Era odyssey through fifty towns where Bach resided, visited, and of course created his works. Drawing on established sources as well as newly available East German archives, the authors describe each site in Bach's time and the present, linking the sites to the biographical information, artistic and historic landmarks, and musical activities associated with each. A wealth of historical illustrations, color photographs, and maps supplement the text, whetting the appetite of the visitor and the armchair traveler alike.